The Debate Concerning Creation in Relation to Ecology - Śledziewski, Sławomir (Studia Ecologiae et Bioethicae, 2006)
The subject of creation was neglected in theological debate for a long time. Only about 35 years ago, when the so-called ecological crisis manifested itself, creation began to appear in the center of theological interest. Some authors tried to accuse Christianity that the theology of creation is responsible for the crisis of the natural environment. Because of this accusation, the science of creation had to take a stand on the issue of ecology. The future of the Earth and its inhabitants depends not on the beginnings of the Universe, but on our present-day actions and attitudes. So, the dialog between natural sciences and theology entered the so-called „third phase” of their relation: the phase of necessary collaboration in the ecological crisis, the dialog between theology and natural sciences must have an ecological character, for at stake is the common future of this world, in which natural sciences and technology are part of God’s creation.